2002
DOI: 10.1029/2001gl014093
|View full text |Cite
|
Sign up to set email alerts
|

Renewal of the bottom water after the winter 2000–2001 may spin‐up the thermohaline circulation in the Japan Sea

Abstract: The newly formed bottom water in the Japan Sea was observed in the summer of 2001 after the severe winter 2000–2001. The new bottom water, which was observed in the northwestern Japan Sea, showed low temperature, high salinity, high dissolved oxygen and low nutrients concentration compared to the old bottom water. The distribution of the new bottom water indicates that the bottom water was formed in the south off Vladivostok, not in the northern Japan Sea north of 43°N, and was advected to the observation area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 14 publications
4
48
0
Order By: Relevance
“…This event was identified from water column anomalies of chemical tracers (dissolved oxygen, nutrients, and chlorofluorocarbons) just above the seafloor in the coastal zone off Vladivostok in the summer of 2001 (Kim et al, 2002;Senjyu et al, 2002;Talley et al, 2003;Tsunogai et al, 2003). By using moored current meters, Senjyu et al (2002) observed strong bottom currents up to 8 cm s −1 from mid-February 2001, suggesting a spin-up of the thermohaline circulation in the Japan Sea. These physicochemical observations demonstrated that the abyssal circulation pattern (conveyor belt) of the Japan Sea could shift immediately as a response to major changes in climate and weather conditions.…”
Section: Temporal Change Of the Japan Sea Bottom Watermentioning
confidence: 99%
“…This event was identified from water column anomalies of chemical tracers (dissolved oxygen, nutrients, and chlorofluorocarbons) just above the seafloor in the coastal zone off Vladivostok in the summer of 2001 (Kim et al, 2002;Senjyu et al, 2002;Talley et al, 2003;Tsunogai et al, 2003). By using moored current meters, Senjyu et al (2002) observed strong bottom currents up to 8 cm s −1 from mid-February 2001, suggesting a spin-up of the thermohaline circulation in the Japan Sea. These physicochemical observations demonstrated that the abyssal circulation pattern (conveyor belt) of the Japan Sea could shift immediately as a response to major changes in climate and weather conditions.…”
Section: Temporal Change Of the Japan Sea Bottom Watermentioning
confidence: 99%
“…/NÞÞ of warm updrafts at 0:1z i and 0:2z i among our case (Jsea), GALE case (Chou and Zimmerman 1989), and AMTEX case (Mahrt and Paumier 1984 Senjyu et al (2002) and Tsunogai et al (2003).…”
Section: Comparison With Other Oceansmentioning
confidence: 99%
“…Cold, saline water (Japan Sea Proper Water, JSPW) is produced there by intense cooling and evaporation at the sea surface. Brine ejection, associated with sea-ice formation off Vladivostok, also facilitates JSPW formation (Senjyu et al 2002;Tsunogai et al 2003). Aircraft observations upstream of this region, will help to define surface turbulent heat fluxes during cold-air outbreaks, furthering the understanding of air-sea interactions in the Sea of Japan.…”
Section: Introductionmentioning
confidence: 99%
“…When applied to the East Sea, the model predicts along-slope currents over the bottom slope of order 10 cm/sec with a much larger peak in winter. It demonstrates that even a small amount of deep-water formation can generate significantly strong abyssal circulation in basins where geostrophic contours close on themselves, supporting the possibility that abyssal circulation is driven by unsteady sources in the East Sea, as suggested by Senjyu et al (2002). It is noted that this model addresses only the basin-scale qualitative feature of real situations, and cannot resolve other detailed features, such as the abnormally strong current over the flat bottom and various eddy-like or fluctuating currents observed in the Japan Basin (Takematsu et al 1999).…”
Section: Discussionmentioning
confidence: 55%
“…In fact, the model is idealized and gives only qualitative features of real situations. Nevertheless, it demonstrates that even small amounts of deep-water formation can generate significantly strong abyssal circulation in basins where geostrophic contours close on themselves, supporting the possibility that abyssal circulation can be driven by unsteady sources in the East Sea, as suggested by Senjyu et al (2002).…”
Section: Applicability To the East Seamentioning
confidence: 94%